PENGARUH ELEMEN BAURAN PEMASARAN PRODUK PASTA GIGI SENSODYNE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN - Kristoforus Andre; Margaretha Sumaryati (Jurnal Manajemen, 2013)
This study aims to determine the effect of marketing mix elements of Sensodyne toothpaste on consumer purchasing decision. Marketing mix consists of product, price, distribution, and promotion which can be controlled by the company and being used to influence consumer purchasing decision. On the other hand, consumer sees the marketing mix as the appeal of a product. Sample collection was done by distributing questionnaires to 100 respondents with Convenience sampling method. Then, the data is processed by using SPSS version 18.0. Results from this study showed that the variables of the marketing mix (product, price, distribution, and promotion) simultaneously have a significant influence on purchasing decision of Sensodyne toothpaste. Partially, there are two variables that have no significant effect, which are distribution and promotion, while two other variables significantly influence consumer purchasing decision. The most influential variable is the variable of product.